Antimony fluoride (SbF3): A potent hole suppressor for tin(II)‐halide perovskite devices. Issue 1 (19th November 2022) - Liu, Ao; Zhu, Huihui; Kim, Soonhyo; Reo, Youjin; Kim, Yong‐Sung; Bai, Sai; Noh, Yong‐Young
Abstract: Tin (Sn 2+ )‐based halide perovskites have been developed as the most promising alternatives to their toxic Pb‐based counterparts in optoelectronic devices. However, the facile tin vacancy formation and easy oxidization characteristics make Sn 2+ ‐based perovskites highly p‐doped with excessive hole concentrations, which significantly hinder their applications. Herein, we demonstrate a potent hole inhibitor of antimony fluoride (SbF3 ), which possesses a higher hole‐suppression capability than conventional tin fluoride (SnF2 ). A small amount of SbF3 allows a wide range of hole‐density modulation with no or less SnF2 addition, thus mitigating the negative effects of using only SnF2 . A SnF2 /SbF3 co‐additive approach was further developed to achieve high‐performance Sn 2+ perovskite thin‐film transistors operated in the enhancement mode with a five‐fold enhancement of the field‐effect mobility and improved operational stability compared to using only SnF2 . We expect that the SbF3 hole suppressor and co‐additive approach can provide opportunities for the development of high‐efficiency Sn 2+ ‐perovskite optoelectronic devices. Abstract : A novel potent hole suppressor of SbF3 was developed for Sn 2+ ‐based halide perovskites. SbF3 can mitigate the negative effect of using single SnF2, enabling the high‐performance enhancement‐mode Sn 2+ ‐perovskite thin‐film transistors.